Mycorrhizal fungal abundance is affected by long‐term climatic manipulations in the field - Philip L. Staddon; Ken Thompson; Iver Jakobsen; J. Philip Grime; Andrew P. Askew; Alastair H. Fitter (Global Change Biology, 2003)
Climate change treatments – winter warming, summer drought and increased summer precipitation – have been imposed on an upland grassland continuously for 7 years. The vegetation was surveyed yearly. In the seventh year, soil samples were collected on four occasions through the growing season in order to assess mycorrhizal fungal abundance. Mycorrhizal fungal colonisation of roots and extraradical mycorrhizal hyphal (EMH) density in the soil were both affected by the climatic manipulations, especially by summer drought. Both winter warming and summer drought increased the proportion of root length colonised (RLC) and decreased the density of external mycorrhizal hyphal. Much of the response of mycorrhizal fungi to climate change could be attributed to climate‐induced changes in the vegetation, especially plant species relative abundance. However, it is possible that some of the mycorrhizal response to the climatic manipulations was direct – for example, the response of the EMH density to the drought treatment. Future work should address the likely change in mycorrhizal functioning under warmer and drier conditions.

Mycorrhizas and global environmental change: research at different scales - P. L. Staddon; A. Heinemeyer; A. H. Fitter (Plant and Soil, 2002)